Double Bertrand tax competition: a fiscal game with governments acting as middlemen - Andreas Wagener (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In a common market with costless mobility of all factors, regional governments can attract mobile firms by granting subsidies which must be financed out of wage taxes on mobile labour. Since firms locate where subsidies are highest and workers settle where taxes are lowest, government are forced "in the splits" (double Bertrand-type tax competition). We assume that without government intervention there is unemployment in the economy. Then regional governments behave like middlemen in the (distorted) labour market and the fiscal game takes the form of competition among strategic intermediaries. Results from the theory of intermediation are applied to this framework, enabling us to explain why government size may increase rather than decline under the the pressures of ongoing economic integration, how industrial clustering may emerge from tax competition, or how unemployment can be turned into job vacancies.
Keywords: H77; 330; Tax Competition; Fiscal Games; Subsidy Wars; Steuerwettbewerb; Subvention; Standortwettbewerb; Wirtschaftsunion; Spieltheorie; Regionalpolitik; Makler; Theorie